ANALISIS PENCATATAN DAN PELAPORAN ASET TETAP PADA PEMERINTAH KABUPATEN KEPULAUAN SANGIHE TAHUN 2011 (STUDI KASUS PADA DINAS PPKAD SELAKU SKPKD) - Mogi, Deasy Anastasia; Morasa, Jenny (ACCOUNTABILITY, 2013)
Local governments are reguired to make accountability reports that use accounting system that is set by the central government in the form of law – laws and regulations that are binding on all Government local government. Therefore, each Regional Financial Management Unit  ( SKPKD )  must prepare its financial statements based on the government regulation number 24 of the Minister of home affairs Number 59 year 2007, which is an amandement to Permendagri N0. 13 year 2006 on guidelines financial Management.The research was conducted in Sangihe regency, which in this study, analyzed fixed asset Recording and Reporting on Local Government in this case the Departement of finance and revenue management as a Regional Asset SKPKD for fiscal year 2011.The purpose of this study is to analyzed the suitability of the recording and reporting of fixed assets in Sangihe regency government especially the Departement of revenue in the finance and asset management areas as SKPKD to financial statements in  financial report balance Sangihe islanda District government with government regulation No. 24 year 2005 on standards government accounting and No. 13 year 2006 on Regional Financial Management Guidelslines.The study uses a descriptive research design in the form of case studies. Type of data used is quantitative data that figures-figures in the Balance sheet. The author uses the method library research, field surveys, and documentation required for data collection.The results showed that, Sangihe regency government has done the recording and reporting of fixed assets with good, though not fully in accordance with government  Regulation No. 24 year 2005 regarding the Regulation of the minister and the government accounting standards of 2007 because the 2011 financial statements opinion gets no opinion  ( Disclaimer Opinion)  by CPC caused by asset accounting. However, the financial statements have been prepared in time to be used for the users as decision makers and as refence for the preparation of financial statements with fiscal year 2012 and in accordance with government accounting standards.